2019
DOI: 10.7717/peerj.7062
|View full text |Cite
|
Sign up to set email alerts
|

SMRT sequencing analysis reveals the full-length transcripts and alternative splicing patterns in Ananas comosus var. bracteatus

Abstract: Background Ananas comosus var. bracteatus is an herbaceous perennial monocot cultivated as an ornamental plant for its chimeric leaves. Because of its genomic complexity, and because no genomic information is available in the public GenBank database, the complete structure of the mRNA transcript is unclear and there are limited molecular mechanism studies for Ananas comosus var. bracteatus. Methods Three size fractionated full-length cDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Similarly, in tomato, moso bamboo, and A. comosus var. bracteatus, researchers have reported that AS genes and non-AS genes have no differences in splicing site selection (Zhao et al, 2018;Clark et al, 2019;Ma et al, 2019). Moreover, we found that short exons tended to be skipped, while short introns tended to be retained ( Figures 10A, B).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Similarly, in tomato, moso bamboo, and A. comosus var. bracteatus, researchers have reported that AS genes and non-AS genes have no differences in splicing site selection (Zhao et al, 2018;Clark et al, 2019;Ma et al, 2019). Moreover, we found that short exons tended to be skipped, while short introns tended to be retained ( Figures 10A, B).…”
Section: Discussionmentioning
confidence: 52%
“…These results are consistent with findings obtained for tomato and Ananas comosus var. bracteatus (Clark et al, 2019;Ma et al, 2019).…”
Section: Differences Between As Genes and Non-as Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are largely involved in regulating plant development and growth, secondary metabolism, and the plant stress response 44 . Recently, an increasing number of studies have focused on the functions of lncRNAs in plants such as in red pineapple 45 and hot pepper 46 . However, no lncRNAs from Rhododendron have been reported.…”
Section: Searching Item Numbersmentioning
confidence: 99%
“…The assembly genome of Huagu11 had the highest continuity than previous genomes, which should be attributed to the use of the SMRT sequencing and Hi-C [ 24 ]. The genome of Yugu1 was based on the sanger sequencing technology [ 9 ], while Zhanggu and TT8 were based on the whole genome shotgun–next-generation sequencing strategy.…”
Section: Resultsmentioning
confidence: 99%